2019
DOI: 10.1515/cclm-2019-0789
|View full text |Cite
|
Sign up to set email alerts
|

Childhood obesity: an overview of laboratory medicine, exercise and microbiome

Abstract: In the last few years, a significant increase of childhood obesity incidence unequally distributed within countries and population groups has been observed, thus representing an important public health problem associated with several health and social consequences. Obese children have more than a 50% probability of becoming obese adults, and to develop pathologies typical of obese adults, that include type 2-diabetes, dyslipidemia and hypertension. Also environmental factors, such as reduced physical activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 252 publications
(272 reference statements)
1
13
0
Order By: Relevance
“…High-fat diet induced obesity in particular results in perturbations of the gut-microbial composition and the depletion of microbial diversity [ 38 , 61 , 62 ]. In line with accumulating evidence [ 10 , 12 , 60 , 63 ], we show that higher BMIZ score is consistently associated with taxonomic shifts. In the low SES group, where the prevalence of obesity was significantly higher, we detected a strong reduction in bacterial diversity and altered bacterial composition among obese children, in line with accumulating data worldwide.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…High-fat diet induced obesity in particular results in perturbations of the gut-microbial composition and the depletion of microbial diversity [ 38 , 61 , 62 ]. In line with accumulating evidence [ 10 , 12 , 60 , 63 ], we show that higher BMIZ score is consistently associated with taxonomic shifts. In the low SES group, where the prevalence of obesity was significantly higher, we detected a strong reduction in bacterial diversity and altered bacterial composition among obese children, in line with accumulating data worldwide.…”
Section: Discussionsupporting
confidence: 92%
“…The intestinal microbiome plays a pivotal role in the maintenance of human metabolic homeostasis and might increase the risk of metabolic and obesity-related complications [ 60 ]. Although there is a lack of consensus on the obese-type microbiome configuration, taxonomic and functional alterations, including reduced biodiversity, have been suggested to contribute to the pathogenesis of obesity in both humans and animal models [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, obesity and sedentariness represent two fundamental factors in the onset of pathologies, such as cardiovascular [29,30] and respiratory disease [31]. During the quarantine, it has been shown that obese patients are exposed to an increased risk of severe respiratory, even if the link between the obesity and the severity of COVID-19 is unclear [32].…”
Section: Discussionmentioning
confidence: 99%
“…Childhood obesity is a risk factor for insulin resistance and the development of DM in older ages. [14] Llewelyn et al reported that a significant relationship exists between childhood obesity and the development of type 2 DM. [15] *Independent sample t test, † Mann Whitney U test.…”
Section: Discussionmentioning
confidence: 99%